Effect of Mineral Suplement in the Diet for Penaeus monodon F. Shrimp Culture in a Low Salinity Medium - Djuwito Djuwito; Sutrisno Anggoro; Johanes Hutabarat (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2014)
Shrimp culture in a low salinity medium has been developed widely such as in Thailand, China, Indonesia and some Federal country of USA. This new approach of shrimp culture of the tiger prawn Penaeus monodon Fab was done as low salinity shrimp farming; low-salinity inland system, inland shrimp farming, and inland culture. Water source was then treated with a step-wise dilution process with river waters to the salinity range of 25-30 ppt to be used for post-larval rearing and growing. The process of dilution will continue to salinity of 5 ppt to be used for the growing ponds until harvest. The relocation of conventional brakish water ponds for shrimp culture from coastal area to inland area was initially caused by the problems of desease, marine pollutions, environmental issues such as mangrove destructions issues and the change of spatial planning in coastal area. The aim of the study is known the effect of K+ and Mg2+ addition and its combination to the weekly growth rate (based on weight) of the shrimp and Osmotic Capacity. The study using addition of mineral in the diet with assumtion that this approach will have more effective effects to the specific growth rate (SGR), Absolute Growth (∆G), survival rate (SR) and osmotic capability (OC) of the shrimp. The experiment design was Complete Random Design with 3 replicates for each treatment. Treatment A: standard diet added with 1% K (1 gr KCl/100 gr diet), treatment B: standard diet adde with 1% Mg2+ (1 gr dolomite/100 gr diet), treatment C was a combined of 0.5% K+ and 0.5% Mg2+, and treatment D was standard diet without mineral (as control). Result of data analysis using ANOVA revealed that all mineral diet treatment had no significant effect (P > 0.05) to SGR and ∆G for Penaeus monodon cultured in low salinity. Although a combined mineral (K and Mg) treatment C had shows the highest of absolute growth (0.7023 gr) then followed by treatment A (0.6421 gr), B (0.5303 gr), and D (0.4951 gr). The treatment of C with combination of 0.5% K and 0.5% Mg had gave the highest absolute growth and provide the best result. The weekly specific growth rate (SGR) had shown a steady decreasing pattern, with the lowest rate in week-5 and increase again in week-6. All mineral suplement in the diet had revealed a significant effect to the osmoregulatory capacity (OC) with (P value < 0.05) with seawater medium variabel as already mentions earlier. All treatments had gave high survival rate (SR) of the Penaeus monodon post-larvae where treatment A: 95.83%; B: 5.83%; C: 91.67% and control D : 85.50%. Key words: Penaeus monodon F., Mineral, supplements, diet, low-salinity culture